2018
DOI: 10.4143/crt.2017.174
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of and Attitudes toward Human Papillomavirus Vaccination among Adults in Korea: 9-Year Changes in Nationwide Surveys

Abstract: PurposeHuman papillomavirus (HPV) vaccination has been included in the National Immunization Program in Korea since 2016. We aimed to evaluate changes in the awareness of and attitudes toward HPV vaccination, among adults in Korea since the first introduction of the vaccines in 2007.Materials and MethodsA nationwide population-based survey was conducted in 2016 for 1,200 nationally representative Korean men and women; the data obtained were compared with the data from the nationwide survey conducted in 2007.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
4
21
0
Order By: Relevance
“…Here, we found that women with moderate education showed the highest acceptance, indicating that inadequate education might also be a barrier due to insufficient awareness of HPV and its vaccine. High willingness to have daughters vaccinated was also strongly correlated with HPV awareness, and mothers' consciousness of the fact that HPV vaccine can prevent cervical cancer, as found in previous studies [30,34]. Even though mother's awareness of HPV and its vaccine did facilitate HPV vaccination, the uptake of the HPV vaccine might depend on the establishment of a vaccination programme by the government: in Kenya, the awareness of a vaccination programme had great impact on the uptake of HPV vaccination rather than on HPV vaccine acceptance [35].…”
Section: Discussionsupporting
confidence: 71%
“…Here, we found that women with moderate education showed the highest acceptance, indicating that inadequate education might also be a barrier due to insufficient awareness of HPV and its vaccine. High willingness to have daughters vaccinated was also strongly correlated with HPV awareness, and mothers' consciousness of the fact that HPV vaccine can prevent cervical cancer, as found in previous studies [30,34]. Even though mother's awareness of HPV and its vaccine did facilitate HPV vaccination, the uptake of the HPV vaccine might depend on the establishment of a vaccination programme by the government: in Kenya, the awareness of a vaccination programme had great impact on the uptake of HPV vaccination rather than on HPV vaccine acceptance [35].…”
Section: Discussionsupporting
confidence: 71%
“…There may be differences in the survey methods used, but the awareness of men in Japan regarding HPV prevention was estimated to be extremely low, compared with that of men in Western countries. A Korean questionnaire study showed that only 25.1% of men wanted to receive the HPV vaccine . Korea and Japan have similar problems regarding their HPV vaccination programs.…”
Section: Discussionmentioning
confidence: 99%
“…A Korean questionnaire study showed that only 25.1% of men wanted to receive the HPV vaccine. 17 Korea and Japan have Table 3 Comparison of knowledge level among subgroups by profession (medical vs laypersons) and gender…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a nationwide survey conducted in 2007, and updated in 2016, showed a significant increase in the awareness of HPV infection (from 13.3% in 2007 to 35.8% in 2016) and the preventive effect of the HPV vaccine (from 8.6% to 36.9%), and a decrease in the willingness to vaccinate against HPV (from 55.0% to 25.8%). Higher education level, awareness of HPV infection and vaccination, and perception of the seriousness of infection were positively associated with the willingness of respondents to vaccinate their daughters [59], [60]. Another nationwide survey in Korea revealed that mothers’ awareness of HPV vaccination is the most important method for preventing cervical cancer in their daughters.…”
Section: Hpv Screening and Vaccination Programme In Koreamentioning
confidence: 99%